Optical glass, preform and optical element
By adjusting the proportion of specific oxide components in the optical glass, the shortcomings of existing optical glass in partial dispersion ratio, devitrification resistance and reheating press molding are solved, and the manufacturing needs of high-precision optical components are achieved.
Patent Information
- Application Number
- CN202411596231.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-07
- Filing Date
- 2020-09-18
- Publication Date
- 2025-02-18
AI Technical Summary
It is difficult for existing optical glasses to achieve partial dispersion ratios within the required range, high devitrification resistance and good reheating press molding, especially when the demand for low dispersion materials increases.
By adjusting the component ratios of SiO2, Nb2O5, ZrO2, Li2O and Ln2O3 in the optical glass, the partial dispersion ratio is ensured to be within a specific range, and the glass is devitrified and reheated press molding properties are improved.
Optical glass with a partial dispersion ratio within the required range has high devitrification resistance and good reheating press molding, and is suitable for the manufacturing of high-precision optical components.
Smart Images

Figure CN119461836A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to optical glass and an optical element. Background Art
[0002] In the optical systems of digital cameras and video cameras, blurring called aberration exists in all images, although the degree of blurring varies. This aberration is classified into monochromatic aberration and chromatic aberration, and chromatic aberration in particular strongly depends on the material properties of the lens used in the optical system.
[0003] Generally, chromatic aberration can be corrected by combining a low-dispersion convex lens and a high-dispersion concave lens, but this combination can only correct the aberrations in the red and green regions, and the aberrations in the blue region still remain. The aberrations in the blue region that are not completely removed are called secondary spectrum. In order to correct the secondary spectrum, it is necessary to consider the trend of the g line (435.835nm) in the blue region for optical design. At this time, the partial dispersion ratio (θg, F) is used as an indicator of optical characteristics that are of concern in optical design. In the above-mentioned optical system in which a low-dispersion lens is combined with a high-dispersion lens, the secondary spectrum can be well corrected by using an optical material with a larger partial dispersion ratio (θg, F) for the lens on the low-dispersion side and an optical material with a smaller partial dispersion ratio (θg, F) for the lens on the high-dispersion side.
[0004] In recent years, in optical design, there is an increasing demand for glass with a small partial dispersion ratio (θg, F).
[0005] The partial dispersion ratio (θg, F) is expressed by the following equation (1).
[0006] θg,F=(n g -n F ) / (n F -n C ) ······ (1)
[0007] In optical glass, the partial dispersion ratio (θg, F) and the Abbe number (ν d ) has a nearly linear relationship. The straight line representing this relationship is a line with the vertical axis representing the partial dispersion ratio (θg, F) and the horizontal axis representing the Abbe number (ν d ), the partial dispersion ratios of NSL7 and PBM2 and the Abbe number are plotted on the orthogonal coordinates of , and the straight line connecting the two points is represented and called the standard line. The standard glass used as the basis for the standard line varies depending on the optical glass manufacturer, but each company uses roughly the same slope and intercept to define it (NSL7 and PBM2 are optical glasses manufactured by Ohara Co., Ltd., and the Abbe number of PBM2 (ν d) is 36.3, the partial dispersion ratio (θg, F) is 0.5828, and the Abbe number (ν d ) is 60.5, and the partial dispersion ratio (θg, F) is 0.5436. )
[0008] As methods for making optical elements from optical glass, for example, there are known methods of grinding and polishing a blank or glass block formed of optical glass to obtain the shape of an optical element; a method of reheating a blank or glass block formed of optical glass and molding it (reheating and pressing) to obtain a glass molded body, and grinding and polishing the glass molded body; and a method of molding a preformed body obtained from a blank or glass block in a mold obtained by ultra-precision processing (precision press molding) to obtain the shape of an optical element. In any of the methods, it is required that stable glass can be obtained when the blank or glass block is formed from molten glass raw materials. Among them, when the stability (devitrification resistance) of the glass constituting the blank or glass block obtained against devitrification is reduced and crystallization occurs inside the glass, glass suitable for use as an optical element can no longer be obtained.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2006-248897
[0012] Patent Document 2: Japanese Patent Application Publication No. 2012-240909
[0013] It is difficult to obtain the glass of Patent Document 1 having a small partial dispersion ratio (θg, F), and the devitrification property is also likely to be poor.
[0014] The glass of Patent Document 2 also aims to solve the technical problem of reducing the partial dispersion ratio (θg, F), but since it contains Ta2O5 as an essential component, it not only has a high manufacturing cost, but also has poor formability due to its poor meltability. Summary of the invention
[0015] Technical problem to be solved by the invention
[0016] The present invention has been made in view of the above-mentioned technical problems, and an object of the present invention is to obtain an optical glass having a partial dispersion ratio (θg, F) within a desired range, high resistance to devitrification, and good reheating press moldability.
[0017] More specifically, it is to obtain a partial dispersion ratio (θg, F) and the Abbe number (ν d ) and satisfy (-0.00162×ν d +0.624≤(θg,F)≤(-0.00162×νd +0.654), and the liquidus temperature is below 1150°C, and the reheating press moldability is good.
[0018] Solutions to technical problems
[0019] The inventors conducted intensive experimental studies to solve the above-mentioned technical problems and found that by adjusting the relationship between the contents of Ln2O3 and LiO2 in a glass containing SiO2 and Nb2O5 components, an optical glass having a low partial dispersion ratio, high resistance to devitrification and good reheating pressing characteristics can be produced, thereby completing the present invention.
[0020] (1) An optical glass comprising, in terms of mass % of oxide-converted composition:
[0021] 10.0~35.0% SiO2 content,
[0022] 10.0~40.0% Nb2O5 component,
[0023] 1.0~15.0% ZrO2 component,
[0024] 1.0 to 15.0% Li2O content, and
[0025] 1.0 to 20.0% of Ln2O3 (wherein Ln is at least one selected from the group consisting of La, Y, Gd, and Yb),
[0026] The mass ratio (Li2O+La2O3) / SiO2 is 0.35 or more,
[0027] The mass ratio Li2O / (Li2O+Na2O+K2O) is 0.50 or more,
[0028] Partial dispersion ratio (θg, F) and Abbe number (ν d ) and satisfy (-0.00162×ν d +0.624≤(θg,F)≤(-0.00162×ν d +0.654).
[0029] (2) The optical glass according to (1), which contains, in terms of mass % of the oxide conversion composition:
[0030] 0~20.0% B2O3 content,
[0031] 0~20.0% La2O3 content,
[0032] 0~20.0% CaO content,
[0033] 0~20.0% SrO component,
[0034] 0~20.0% BaO component,
[0035] 0~10.0% Na2O content.
[0036] (3) The optical glass according to (1) or (2), wherein:
[0037] Compared with B2O3, it contains more SiO2.
[0038] The mass ratio (ZnO+TiO2+P2O5) / (ZrO2+La2O3+LiO2) is less than 0.15,
[0039] The mass and BaO+CaO+SrO are 5.0~20.0%.
[0040] (4) The optical glass according to any one of (1) to (3), wherein the refractive index (n d ) is 1.70000~1.80000, and the Abbe number (ν d ) is 30.00~40.00.
[0041] (5) The optical glass according to any one of (1) to (4), wherein the liquidus temperature is 1150° C. or lower.
[0042] (6) An optical element made of the optical glass described in any one of (1) to (5).
[0043] (7) A preform for grinding and / or precision press molding, made of the optical glass described in any one of (1) to (5).
[0044] (8) An optical device comprising the optical element described in (6) or (7).
[0045] According to the present invention, it is possible to obtain an optical glass having a low partial dispersion ratio (θg, F), a low liquidus temperature, and good reheating press moldability. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 The partial dispersion ratio (θg, F) and the Abbe number (ν d )’s relationship diagram. DETAILED DESCRIPTION
[0047] Hereinafter, the embodiments of the optical glass of the present invention will be described in detail, but the present invention is not limited to the following embodiments, and can be appropriately changed and implemented within the scope of the purpose of the present invention. It should be noted that the description of the repeated parts may be appropriately omitted, which will not limit the purpose of the invention.
[0048] [Glass composition]
[0049] The composition range of each component constituting the optical glass of the present invention is as follows. In this specification, unless otherwise specifically denied, the content of each component is expressed in terms of mass % of the oxide-converted composition relative to the total mass of the glass. Here, the "oxide-converted composition" means that the composition of each component contained in the glass electrolyte is expressed by assuming that the oxides, complex salts, metal fluorides, etc. used as raw materials of the glass composition components of the present invention are all decomposed and converted into oxides during melting, and the total mass of the generated oxides is recorded as 100 mass %.
[0050] <About essential ingredients and optional ingredients>
[0051] SiO2 is an essential component that promotes stable glass formation and reduces devitrification (generation of crystals) that is undesirable as an optical glass.
[0052] In particular, by making the content of SiO2 component 10.0% or more, it is possible to obtain glass with not only a greatly improved partial dispersion ratio but also excellent resistance to devitrification. In addition, the liquidus temperature can be lowered. Therefore, the lower limit of the content of SiO2 is preferably 10.0% or more, more preferably 13.0% or more, still more preferably 15.0% or more, further preferably 18.0% or more, and most preferably 20.0% or more.
[0053] On the other hand, by making the content of SiO2 component 35.0% or less, the increase of partial dispersion ratio can be suppressed. Therefore, the upper limit of the content of SiO2 component is preferably 35.0% or less, more preferably 33.0% or less, and most preferably 31.0% or less.
[0054] Nb2O5 is an essential component, and can increase the refractive index and reduce the Abbe number.
[0055] In particular, the refractive index can be increased by making the content of Nb2O5 component 10.0% or more. Therefore, the lower limit of the content of Nb2O5 component is preferably 10.0% or more, more preferably 12.0% or more, still more preferably 15.0% or more, further preferably 20.0% or more, and most preferably 23.0% or more.
[0056] On the other hand, by making the content of Nb2O5 component less than 40.0%, thermal stability can be obtained, and the material cost of glass can be reduced. Furthermore, the devitrification of glass can be reduced. Therefore, the upper limit of the content of Nb2O5 component is preferably less than 40.0%, more preferably less than 38.0%, even more preferably less than 36.0%, and most preferably less than 34.0%.
[0057] ZrO2 is an essential component, which can increase the refractive index and Abbe number of the glass and reduce the partial dispersion ratio.
[0058] In particular, by making the content of ZrO2 component 1.0% or more, the partial dispersion ratio can be reduced and a stable glass can be obtained. Therefore, the content of ZrO2 component has a lower limit of preferably 1.0% or more, more preferably 2.0% or more, still more preferably 3.0% or more, further preferably 5.0% or more, and most preferably 6.0% or more.
[0059] On the other hand, by making the content of ZrO2 component 15.0% or less, devitrification can be reduced, and more homogeneous glass can be easily obtained. Therefore, the upper limit of the content of ZrO2 component is preferably 15.0% or less, more preferably 12.0% or less, still more preferably 11.0% or less, further preferably 10.0% or less, and most preferably 9.0% or less.
[0060] The Li2O component, unlike other alkali metals, is an essential component capable of reducing the partial dispersion ratio.
[0061] In particular, by making the content of Li2O component 1.0% or more, the meltability of glass can be improved and the partial dispersion ratio can be reduced. Therefore, the lower limit of the content of Li2O component is preferably 1.0% or more, more preferably 1.5% or more, still more preferably 2.0% or more, and most preferably 2.5% or more.
[0062] On the other hand, by making the content of the Li2O component 15.0% or less, devitrification due to excessive content can be reduced, and devitrification during reheating and pressing can also be reduced.
[0063] Therefore, the upper limit of the content of the Li2O component is preferably 15.0% or less, more preferably 12.0% or less, still more preferably 10.0% or less, further preferably 9.0% or less, and most preferably 8.0% or less.
[0064] The B2O3 component is an optional component, which promotes stable glass formation, lowers the liquidus temperature, improves the resistance to devitrification, and improves the solubility of glass raw materials.
[0065] In particular, by making the content of B2O3 component 0% or more, the rise of liquidus temperature can be suppressed. Therefore, the content of B2O3 component is preferably 0% or more, more preferably greater than 0%, more preferably 0.1% or more, further preferably 0.2% or more, and most preferably 0.3% or more.
[0066] On the other hand, by making the content of B2O3 component 20.0% or less, the decrease of refractive index can be suppressed, and the increase of partial dispersion ratio can be suppressed. Therefore, the upper limit of the content of B2O3 component is preferably 20.0% or less, more preferably 18.0% or less, still more preferably 16.0% or less, still more preferably 14.0% or less, further preferably 12.0% or less, and most preferably 11.0% or less.
[0067] It is preferred to contain more SiO2 than B2O3. When the B2O3 content is greater than the SiO2 content, the partial dispersion ratio increases. Therefore, by containing more SiO2 than the B2O3 content, the glass can be stabilized and the partial dispersion ratio can be reduced at the same time.
[0068] The La2O3 component is a component that can reduce devitrification and decrease the partial dispersion ratio. The inclusion of this component can produce an effect different from other rare earth components that are prone to devitrification.
[0069] In particular, by making the content of the La2O3 component 0% or more, the refractive index can be increased, and by adjusting within the range of the composition of the present invention, the anomalous dispersion can be reduced. Therefore, the content of the La2O3 component is preferably 0% or more, more preferably 1.0% or more, more preferably 2.0% or more, further preferably 3.0% or more, further preferably 4.0% or more, and most preferably 5.0% or more.
[0070] On the other hand, by making the content of La2O3 component 20.0% or less, the increase of Abbe number can be suppressed, devitrification can be reduced, and coloration can be reduced. Therefore, the upper limit of the content of La2O3 component is preferably 20.0% or less, more preferably 19.0% or less, still more preferably 17.0% or less, and most preferably 16.0% or less.
[0071] The Gd2O3 component, the Y2O3 component, and the Yb2O3 component are arbitrary components, and when the content of any one of them is at least greater than 0%, the refractive index can be increased and the partial dispersion ratio can be reduced.
[0072] On the other hand, when a large amount of Gd2O3, Y2O3 and Yb2O3 components are contained, the liquidus temperature is lowered and the glass is devitrified.
[0073] In particular, by making the contents of the Gd2O3 component, the Y2O3 component and the Yb2O3 component respectively 10.0% or less, devitrification can be reduced and coloration can be reduced. Therefore, the upper limit of the contents of the Gd2O3 component, the Y2O3 component and the Yb2O3 component is preferably 10.0% or less, more preferably 8.0% or less, further preferably 5.0% or less, and most preferably 3.0% or less.
[0074] The Na2O component and the K2O component are optional components, and when the content thereof is greater than 0%, the meltability of the glass raw material can be improved and coloring can be reduced.
[0075] On the other hand, when Na2O and K2O are contained in large amounts, the stability of the glass deteriorates and the resistance to devitrification decreases.
[0076] On the other hand, by making the content of Na2O component and K2O component 10.0% or less, devitrification can be reduced. Therefore, the upper limit of the content of Na2O component and K2O component is preferably 10.0% or less, more preferably 8.0% or less, still more preferably 7.0% or less, further preferably 6.0% or less, and most preferably 5.0% or less.
[0077] The MgO component is an arbitrary component that can improve solubility and lower the liquidus temperature. However, when the MgO component is contained in a large amount, the glass will devitrify.
[0078] On the other hand, devitrification can be reduced by making the content of the MgO component 10.0% or less. Therefore, the upper limit of the content of the MgO component is preferably 10.0% or less, more preferably 8.0% or less, still more preferably 5.0% or less, further preferably 3.0% or less, and most preferably 2.0% or less.
[0079] The CaO component is an optional component, and can improve the stability of glass.
[0080] In particular, the melting property can be improved by making the content of the CaO component 0% or more. Therefore, the lower limit of the content of the CaO component is preferably 0% or more, more preferably 0.1% or more, still more preferably 0.5% or more, further preferably 1.0% or more, and most preferably 2.0% or more.
[0081] On the other hand, by making the content of the CaO component 20.0% or less, the press moldability becomes better and the increase of the partial dispersion ratio can be suppressed. Therefore, the upper limit of the content of the CaO component is preferably 20.0% or less, more preferably 17.0% or less, still more preferably 14.0% or less, further preferably 12.0% or less, and most preferably 10.0% or less.
[0082] The SrO component is an optional component, and can improve the stability of glass.
[0083] On the other hand, by making the content of the SrO component 20.0% or less, the press moldability becomes better and the increase of the partial dispersion ratio can be suppressed. Therefore, the upper limit of the content of the SrO component is preferably 20.0% or less, more preferably 17.0% or less, still more preferably 14.0% or less, further preferably 12.0% or less, and most preferably 10.0% or less.
[0084] The BaO component is an optional component, and can improve the stability of glass.
[0085] On the other hand, by making the content of BaO component 20.0% or less, press moldability becomes better and the increase of partial dispersion ratio can be suppressed. Therefore, the upper limit of the content of BaO component is preferably 20.0% or less, more preferably 17.0% or less, still more preferably 14.0% or less, further preferably 12.0% or less, and most preferably 10.0% or less.
[0086] The TiO2 component is an arbitrary component that can increase the refractive index and reduce the Abbe number. On the other hand, when the TiO2 component is contained in a large amount, the partial dispersion ratio becomes large.
[0087] In particular, by making the content of TiO2 component 10.0% or more, the increase of partial dispersion ratio can be suppressed and the Abbe number can be reduced. Therefore, the upper limit of the content of TiO2 component is preferably 10.0% or less, more preferably 5.0% or less, still more preferably 3.0% or less, and most preferably 2.0% or less.
[0088] The ZnO component is an optional component that is inexpensive and can adjust the glass to a high dispersion side. On the other hand, when the ZnO component is contained in a large amount, the partial dispersion ratio increases.
[0089] In particular, by making the content of the ZnO component 10.0% or less, devitrification and coloring can be reduced. Therefore, the upper limit of the content of the ZnO component is preferably 10.0% or less, more preferably 5.0% or less, still more preferably less than 3.0%, and most preferably 1.0% or less.
[0090] The Ta2O5 component is an optional component, and can increase the refractive index, reduce the Abbe number and the partial dispersion ratio, and improve the resistance to devitrification.
[0091] In particular, by making the content of Ta2O5 component less than 10.0%, the usage of Ta2O5 component as a rare mineral resource can be reduced, and glass is also easily melted at a lower temperature, so the production cost of glass can be reduced. In addition, thereby, the devitrification of glass caused by the excessive content of Ta2O5 component can be reduced. Therefore, the content of Ta2O5 component, its upper limit is preferably less than 10.0%, more preferably less than 5.0%, more preferably less than 3.0%, and most preferably less than 1.0%. In particular, based on the viewpoint of reducing the material cost of glass, it is most preferred not to contain Ta2O5 component.
[0092] The WO3 component is an arbitrary component that can increase the refractive index and reduce the Abbe number, and can improve the solubility of the glass raw material. By making the content of the WO3 component 10.0% or less, it is possible to make the partial dispersion ratio of the glass difficult to increase, and to reduce the coloring of the glass and improve the internal transmittance. Therefore, the upper limit of the content of the WO3 component is preferably 10.0% or less, more preferably 5.0% or less, still more preferably 3.0% or less, and most preferably 1.0% or less.
[0093] The P2O5 component is an optional component and can improve the stability of the glass.
[0094] On the other hand, by making the content of the P2O5 component 10.0% or less, the increase in the partial dispersion ratio caused by the excessive content of the P2O5 component can be reduced. Therefore, the upper limit of the content of the P2O5 component is preferably 10.0% or less, more preferably 5.0% or less, even more preferably 3.0% or less, further preferably less than 2.0%, and most preferably 1.0% or less.
[0095] The GeO2 component is an optional component that can increase the refractive index and reduce devitrification. By making the content of the GeO2 component less than 10.0%, the amount of expensive GeO2 used can be reduced, thereby reducing the material cost of the glass. Therefore, the upper limit of the content of the GeO2 component is preferably less than 10.0%, more preferably less than 5.0%, even more preferably less than 3.0%, and most preferably less than 1.0%.
[0096] The Al2O3 component is an optional component, and can increase the refractive index and improve the resistance to devitrification.
[0097] On the other hand, by making the content of Al2O3 component less than 10.0%, devitrification caused by excessive content of Al2O3 component can be reduced. Therefore, the upper limit of the content of Al2O3 component is preferably less than 10.0%, more preferably less than 5.0%, still more preferably less than 3.0%, and most preferably less than 1.0%.
[0098] The Ga2O3 component is an optional component, and can increase the refractive index and improve the resistance to devitrification.
[0099] On the other hand, by making the content of Ga2O3 component less than 10.0%, devitrification caused by excessive content of Ga2O3 component can be reduced. Therefore, the upper limit of the content of Ga2O3 component is preferably less than 10.0%, more preferably less than 5.0%, still more preferably less than 3.0%, and most preferably less than 1.0%.
[0100] The Bi2O3 component is an arbitrary component that can increase the refractive index and reduce the Abbe number, and can also reduce the glass transition point. By making the content of the Bi2O3 component 10.0% or less, it is possible to make the partial dispersion ratio difficult to increase, and it is possible to reduce the coloring of the glass and increase the internal transmittance. Therefore, the content of the Bi2O3 component is preferably 10.0% or less, more preferably 5.0% or less, even more preferably 3.0% or less, and most preferably 1.0% or less.
[0101] The TeO2 component is an arbitrary component that can increase the refractive index, reduce the partial dispersion ratio, and reduce the glass transition point. By making the content of the TeO2 component less than 10.0%, the coloring of the glass can be reduced and the internal transmittance can be increased. In addition, by reducing the use of the expensive TeO2 component, a glass with a lower material cost can be obtained. Therefore, the upper limit of the content of the TeO2 component is preferably less than 10.0%, more preferably less than 5.0%, even more preferably less than 3.0%, and most preferably less than 1.0%. In particular, based on the viewpoint of reducing the material cost of the glass, the TeO2 component may not be contained.
[0102] SnO2 is an optional component that can clarify the molten glass (defoaming) and improve the visible light transmittance of the glass. By making the content of SnO2 less than 1.0%, it is possible to prevent the coloring of the glass and the loss of clarity of the glass caused by the reduction of the molten glass. In addition, since the alloying of SnO2 with the melting equipment (especially precious metals such as Pt) can be reduced, the life of the melting equipment can be extended. Therefore, the upper limit of the content of SiO2 is preferably less than 1.0%, more preferably less than 0.5%, and further preferably less than 0.1%.
[0103] The Sb2O3 component can promote the defoaming of the glass and make the glass clear, and is an arbitrary component in the optical glass of the present invention. By making the content of the Sb2O3 component less than 1.0% compared to the total mass of the glass, it is possible to prevent excessive foaming during glass melting and to prevent the Sb2O3 component from alloying with melting equipment (especially precious metals such as Pt). Therefore, the upper limit of the content of the Sb2O3 component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 1.0%, more preferably less than 0.5%, even more preferably less than 0.3%, and most preferably less than 0.1%.
[0104] It should be noted that the component that clarifies and defoams the glass is not limited to the above-mentioned Sb2O3 component, and clarifiers, defoamers or combinations thereof known in the field of glass manufacturing can be used.
[0105] When the sum (mass sum) of the contents of the Ln2O3 components (wherein Ln is one or more selected from the group consisting of La, Y, Gd, and Yb) is 1.0% or more, the refractive index can be increased and the partial dispersion ratio can be reduced. Therefore, the lower limit of the sum of the Ln2O3 components is preferably 1.0% or more, more preferably 3.0% or more, further preferably 5.0% or more, and most preferably 7.0% or more.
[0106] On the other hand, by making the sum of the contents (mass sum) of the Ln2O3 component 20.0% or less, devitrification caused by excessive content can be reduced. Therefore, the upper limit is preferably 20.0% or less, more preferably 18.0% or less, still more preferably 17.0% or less, and most preferably 16.0% or less.
[0107] When the sum (mass sum) of the contents of the Rn2O component (wherein Rn is one or more selected from the group consisting of Li, Na, and K) is 1.0% or more, the stability of the glass can be improved. Therefore, the lower limit of the sum of the Rn2O components is preferably 1.0% or more, more preferably 2.5% or more, further preferably 3.0% or more, and most preferably 3.5% or more.
[0108] On the other hand, by making the sum of the contents (mass sum) of the Rn2O component 15.0% or less, the reduction in refractive index can be suppressed, and devitrification caused by excessive content can be reduced. Therefore, the upper limit is preferably 15.0% or less, more preferably 14.0% or less, still more preferably 13.0% or less, and most preferably 12.0% or less.
[0109] When the sum of the contents of RO components (wherein R is one or more selected from the group consisting of Mg, Ca, Sr, and Ba) is 5.0% or more, the low temperature melting property can be improved. Therefore, the sum of the contents of RO components preferably has a lower limit of 5.0%, more preferably 5.3% or more, further preferably 5.8% or more, and most preferably 6.0% or more.
[0110] On the other hand, the sum of the contents of the RO components is preferably 20.0% or less in order to suppress the reduction in devitrification resistance due to excessive content. Therefore, the upper limit of the mass sum of the RO components is preferably 20.0% or less, more preferably 19.0% or less, still more preferably 18.0% or less, and most preferably 16.0% or less.
[0111] When the mass sum of BaO+CaO+SrO is 5.0% or more, the low temperature melting property can be improved. Therefore, the mass sum of BaO+CaO+SrO preferably has a lower limit of 5.0% or more, more preferably 5.3% or more, further preferably 5.8% or more, and most preferably 6.0% or more.
[0112] On the other hand, when the content of BaO+CaO+SrO is excessive, the refractive index and dispersion will increase, it will be difficult to obtain the desired optical properties, and the devitrification will deteriorate, so it is preferably 20.0% or less. Therefore, the upper limit of the content of BaO+CaO+SrO is preferably 20.0% or less, more preferably 19.0% or less, further preferably 18.0% or less, and most preferably 16.0% or less.
[0113] When the mass ratio (Li2O+La2O3) / SiO2 is 0.35 or more, the glass can be stabilized and the partial dispersion ratio can be reduced. Therefore, the lower limit of the mass ratio (Li2O+La2O3) / SiO2 is preferably 0.35 or more, more preferably 0.36 or more, further preferably 0.38 or more, and most preferably 0.40 or more.
[0114] On the other hand, the mass ratio (Li2O+La2O3) / SiO2 is preferably 1.00 or less in order to suppress the increase in liquidus temperature. Therefore, the upper limit of the mass ratio (Li2O+La2O3) / SiO2 is preferably 1.00 or less, more preferably 0.90 or less, further preferably 0.88 or less, and most preferably 0.85 or less.
[0115] When the mass ratio Li2O / (Li2O+Na2O+K2O) is 0.50 or more, the effect of the LiO2 component that reduces the partial dispersion ratio is best, the solubility can be increased, and devitrification can be suppressed. Therefore, the lower limit of the mass ratio Li2O / (Li2O+Na2O+K2O) is preferably 0.50 or more, more preferably 0.52 or more, further preferably 0.54 or more, and most preferably 0.55 or more.
[0116] When the mass ratio (SiO2+B2O3+Ln2O3) / Rn2O is 3.50 or more, devitrification can be suppressed and the liquidus temperature can be lowered. Therefore, the lower limit of the mass ratio (SiO2+B2O3+Ln2O3) / Rn2O is preferably 3.50 or more, more preferably 3.55 or more, further preferably greater than 3.58, and most preferably 3.60 or more.
[0117] On the other hand, when the mass ratio (SiO2+B2O3+Ln2O3) / Rn2O is less than 12.0, the Abbe number (ν d ). Therefore, the upper limit of the mass ratio (SiO2+B2O3+Ln2O3) / Rn2O is preferably 12.0 or less, more preferably 11.80 or less, further preferably 11.50 or less, and most preferably 11.20 or less.
[0118] When the mass ratio (ZnO+TiO2+P2O5) / (ZrO2+La2O3+LiO2) is less than 0.15, the increase in the partial dispersion ratio caused by the ZnO component, the TiO2 component and the P2O5 component can be suppressed. Therefore, the upper limit of the mass ratio (ZnO+TiO2+P2O5) / (ZrO2+La2O3+LiO2) is preferably less than 0.15, more preferably less than 0.12, further preferably less than 0.10, and most preferably less than 0.08.
[0119] <About ingredients that should not be contained>
[0120] Next, components that should not be contained in the optical glass of the present invention and components that are preferably not contained are described.
[0121] Other components can be added as needed within the range that does not impair the characteristics of the glass of the present invention. However, in addition to Ti, Zr, Nb, W, La, Gd, Y, Yb, and Lu, various transition metal components such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag, and Mo have the property of coloring the glass even in a small amount when contained alone or in a composite form, and absorbing light of a specific wavelength in the visible light region. Therefore, it is preferably substantially not contained in optical glasses using wavelengths in the visible light region.
[0122] In addition, since lead compounds such as PbO and arsenic compounds such as As2O3 are components with high environmental burden, it is preferable that they are substantially not contained, that is, they are not contained at all except for unavoidable contamination.
[0123] In addition, Th, Cd, Tl, Os, Be and Se are each considered harmful chemical substances and are therefore avoided in recent years. Environmental measures must be taken not only in the glass manufacturing process but also in the processing process and until the waste treatment after the glass is manufactured. Therefore, when the environmental impact is important, it is preferred that these components are not substantially contained.
[0124] [Manufacturing method]
[0125] The optical glass of the present invention can be produced, for example, as follows. For example, the above raw materials are uniformly mixed so that each component is within a specified content range, and the thus produced mixture is placed in a platinum crucible, a quartz crucible or an alumina crucible for rough melting, and then placed in a gold crucible, a platinum crucible, a platinum alloy crucible or an iridium crucible, and melted at a temperature range of 1000 to 1400° C. for 2 to 5 hours, and then stirred for homogenization and defoaming, etc., and then the temperature is lowered to 950 to 1250° C., and fine stirring is performed to remove grains, and then the mixture is cast into a mold and slowly cooled to produce the glass.
[0126] <Physical Properties>
[0127] The optical glass of the present invention has a refractive index (n d ) and the Abbe number (ν d ).
[0128] The refractive index (n d ), the lower limit of which is preferably 1.70000 or more, more preferably 1.73000 or more, and further preferably 1.75000 or more. The upper limit of the refractive index is preferably 1.80000 or less, and more preferably 1.79000 or less.
[0129] The Abbe number (ν d ), the lower limit of which is preferably 30.00 or more, more preferably 32.00 or more, and still more preferably 33.00 or more. On the other hand, the Abbe number (ν d ), and its upper limit is preferably 40.00 or less, more preferably 38.00 or less, and further preferably 37.00 or less.
[0130] The optical glass of the present invention having such a refractive index and Abbe number is useful in optical design, and in particular, can realize high imaging characteristics and also can realize miniaturization of the optical system, thereby increasing the degree of freedom in optical design.
[0131] The optical glass of the present invention has a relatively low partial dispersion ratio (θg, F).
[0132] More specifically, the partial dispersion ratio (θg, F) of the optical glass of the present invention is preferably 0.560 or more, more preferably 0.565 or more, although the lower limit thereof is not particularly limited. On the other hand, the upper limit of the partial dispersion ratio (θg, F) of the optical glass of the present invention is preferably 0.600 or less, more preferably 0.595 or less, and further preferably 0.593 or less. In addition, the partial dispersion ratio (θg, F) of the optical glass of the present invention is related to the Abbe number (ν d ), preferably satisfying (-0.00162×ν d +0.624)≤(θg,F)≤(-0.00162×ν d +0.654).
[0133] Thus, the optical glass of the present invention has a lower partial dispersion ratio (θg, F) than the conventionally known glass containing a large amount of SiO2 and Nb2O5. Therefore, the optical element formed by the optical glass can be suitably used for correction of chromatic aberration.
[0134] Here, the Abbe number (ν d ) is related to the partial dispersion ratio (θg, F), and although its lower limit is not particularly limited, it is preferably within (-0.00162×ν d +0.624) or more, more preferably (-0.00162×ν d +0.627) or more, and more preferably (-0.00162×ν d On the other hand, the optical glass of the present invention has an Abbe number (ν d The upper limit of the partial dispersion ratio (θg, F) is preferably (-0.00162×ν d +0.654) or less, more preferably (-0.00162×ν d +0.651) or less, and more preferably (-0.00162×ν d +0.648) or less.
[0135] The optical glass of the present invention preferably has a high visible light transmittance, particularly a high transmittance of light on the short wavelength side of visible light, and thus has little coloration.
[0136] In particular, the optical glass of the present invention, when expressed in terms of glass transmittance, has a wavelength (λ 80 ), and its upper limit is preferably below 420nm, more preferably below 417nm, and further preferably below 410nm.
[0137] The upper limit of the shortest wavelength (λ5) when the spectral transmittance of a sample having a thickness of 10 mm in the optical glass of the present invention is 5% is preferably 345 nm or less, more preferably 343 nm or less, and further preferably 342 nm or less.
[0138] Thus, since the absorption edge of the glass is located near the ultraviolet region and the transparency of the glass to visible light is improved, the optical glass can be preferably used as an optical element that transmits light, such as a lens.
[0139] The optical glass of the present invention preferably has a high resistance to devitrification, and more specifically, preferably has a low liquidus temperature.
[0140] That is, the upper limit of the liquidus temperature of the optical glass of the present invention is preferably 1150°C or lower, more preferably 1148°C or lower, and even more preferably 1145°C or lower. Thus, even if the melted glass is discharged at a lower temperature, the crystallization of the produced glass is reduced, so that devitrification when the glass is formed from a molten state can be reduced, and the influence on the optical characteristics of the optical element using the glass can be reduced. In addition, even if the melting temperature of the glass is low, the glass can be molded, so the energy consumed when the glass is molded can be reduced, and thus the manufacturing cost of the glass can be reduced.
[0141] [Preform and optical element]
[0142] For example, a glass molded body can be produced from the produced optical glass by using a compression molding method such as reheating compression molding or precision compression molding. That is, a preform for compression molding is produced from the optical glass, and the preform is reheated and compression molded, and then ground to produce a glass molded body; or, for example, a preform produced by grinding is precision-pressed to produce a glass molded body. In addition, the method for producing a glass molded body is not limited to the above methods.
[0143] The glass molded body produced in this way can be used for various optical elements, and can be used for optical elements such as lenses and prisms, among which it is particularly preferred. As a result, the color blurring caused by chromatic aberration in the transmitted light of the optical system provided with the optical element can be reduced. Therefore, when the optical element is used in a camera, the photographic object can be more accurately represented, and when the optical element is used in a projector, the desired image can be projected more clearly.
[0144] Example
[0145] The compositions of the embodiments (No. 1 to No. 20) of the present invention and the comparative example A, and the refractive index (n d ), Abbe number (ν d ), partial dispersion ratio (θg, F), liquidus temperature, transmittance λ5 and λ 80 The results are shown in Tables 1 and 2. It should be noted that the following examples are only for illustration and are not limited to these examples.
[0146] The glasses of the embodiments and comparative examples are prepared using high-purity raw materials such as oxides, hydroxides, carbonates, nitrates, fluorides and metaphosphate compounds corresponding to the components thereof, which are commonly used in optical glasses. These raw materials are weighed and uniformly mixed in the proportions of the compositions of the embodiments and comparative examples shown in the table, and then put into a stone crucible (a platinum crucible or an alumina crucible may also be used depending on the solubility of the glass). After being melted in an electric furnace for 0.5 to 5 hours at a temperature range of 1100 to 1400°C depending on the melting difficulty of the glass composition, the glass is transferred to a platinum crucible for stirring and homogenization and defoaming, etc. The temperature is then lowered to 1000 to 1200°C and, after stirring and homogenization, is cast into a mold and slowly cooled to produce glass.
[0147] The refractive index (n d ), Abbe number (ν d ) and partial dispersion ratio (θg, F) are measured in accordance with the V-block method specified in JIS B 7071-2:2018. Here, the refractive index (n d ), expressed as the measured value of the d line (587.56nm) of a helium lamp. In addition, the Abbe number (ν d ), using the refractive index for the d-line of a helium lamp (n d ), the refractive index (n F ), the refractive index (n C ) value, according to the Abbe number (ν d )=[(n d -1) / (n F -n C )] is calculated using the formula of θg, F. In addition, the partial dispersion ratio (θg, F) is calculated using the refractive index (n g ), the refractive index (n F ), the refractive index (n C ) value, according to the partial dispersion ratio (θg, F) = (ng -n F ) / (n F -n C ) is calculated using the formula. These refractive indices (n d ), Abbe number (ν d ) and the partial dispersion ratio (θg, F) are obtained by measuring the glass obtained at a slow cooling rate of -25°C / hr.
[0148] And, according to the Abbe number (ν d ) and the value of the partial dispersion ratio (θg, F), and the relationship (θg, F) = -a2×ν d +The intercept b2 when the slope a2 in b2 is 0.00162.
[0149] The transmittance of the glass of the embodiment and the comparative example is measured according to the standard JOGIS02-2003 of the Japan Optical Glass Industry Association. In addition, in the present invention, by measuring the transmittance of the glass, the presence and degree of coloration of the glass can be obtained. Specifically, according to JIS Z8722, the spectral transmittance of the parallel grinding piece with a thickness of 10 ± 0.1 mm from 200 nm to 800 nm is measured, and the wavelength (λ) at which the spectral transmittance is 80% and 5% is obtained. 80 ,λ5).
[0150] The liquidus temperature of the glass of the embodiment and the comparative example was measured by placing the crushed glass sample on a platinum plate at intervals of 10 mm, keeping it in a furnace with a temperature gradient from 800°C to 1200°C for 30 minutes, taking it out, and observing the glass sample with a microscope with a magnification of 80 times for the presence or absence of crystallization after cooling. At this time, the optical glass was crushed into particles with a diameter of about 2 mm as a sample.
[0151]
Table 1
[0152]
[0153]
Table 2
[0154]
[0155] As shown in the table, the optical glass of the embodiments of the present invention has a refractive index (n d ) are all above 1.70000 and all below 1.80000, within the required range.
[0156] In addition, the optical glass of the embodiment of the present invention has an Abbe number (ν d ) are all above 30.00 and below 40.00, which is within the required range.
[0157] As shown in the table, the optical glass of the embodiments of the present invention has an Abbe number (ν d ) and the partial dispersion ratio (θg, F) satisfy the relationship (-0.00162×ν d +0.624)≤(θg,F)≤(-0.00162×ν d +0.654).
[0158] As shown in the table, the liquidus temperature of the optical glass of the embodiment of the present invention is below 1150° C. It can also be inferred that the optical glass of the embodiment of the present invention has better reheating press moldability due to its low liquidus temperature.
[0159] As shown in the table, the wavelength (λ 80 ) are all below 420nm, and the wavelength (λ5) when the spectral transmittance is 5% is all below 345nm.
[0160] The glass of Comparative Example A has a mass ratio (Li2O+La2O3) / SiO2 of less than 0.35, and therefore suffers from severe devitrification and fails to vitrify.
[0161] Although the present invention has been described in detail above for the purpose of illustration, the purpose of this embodiment is only for illustration, and it should be fully understood that those skilled in the art can make many changes to the present invention without departing from the spirit and scope of the present invention.
[0162] The disclosures of the documents described in this specification and the Japanese application specification that is the Paris priority basis of the present application (including the specification, drawings, and claims) are all incorporated herein by reference.
Claims
1. An optical glass, wherein: In terms of mass % of the oxide conversion composition, it contains: 10.0~30.0% SiO2 content, 10.0~40.0% Nb2O5 component, 1.0~15.0% ZrO2 component, 1.0 to 15.0% Li2O content, and 1.0 to 20.0% of Ln2O3, wherein Ln is at least one selected from the group consisting of La, Y, Gd, and Yb, and Does not contain BaO ingredients, and The mass ratio (Li2O+La2O3) / SiO2 is 0.53 or more and 0.83 or less, The mass ratio Li2O / (Li2O+Na2O+K2O) is 0.50 or more, The mass ratio (SiO2+B2O3+Ln2O3) / Rn2O is 3.60 or more and 6.77 or less, wherein Rn is at least one selected from the group consisting of Li, Na, and K, The mass ratio (ZnO+TiO2+P2O5) / (ZrO2+La2O3+LiO2) is less than 0.04, The liquidus temperature is below 1126°C. Partial dispersion ratio (θg, F) and Abbe number (ν d ) and satisfy (-0.00162×ν d +0.624)≤(θg,F)≤(-0.00162×ν d +0.654).
2. The optical glass according to claim 1, wherein: In terms of mass % of the oxide conversion composition, it contains: 0~20.0% B2O3 content, 0~20.0% La2O3 content, 0~20.0% CaO content, 0 to 20.0% SrO, and 0~10.0% Na2O content.
3. The optical glass according to claim 1 or 2, wherein: Compared with B2O3, it contains more SiO2.
4. The optical glass according to claim 1 or 2, wherein: Refractive index (n d ) is 1.70000~1.80000, and the Abbe number (ν d ) is 30.00~40.
00.
5. The optical glass according to claim 3, wherein: Refractive index (n d ) is 1.70000~1.80000, and the Abbe number (ν d ) is 30.00~40.
00.
6. An optical element made of the optical glass according to any one of claims 1 to 5.
7. A preform for grinding and / or precision press molding made of the optical glass according to any one of claims 1 to 5.
8. An optical device comprising the optical element according to claim 6.
Citation Information
Patent Citations
Optical glass, glass gob for press molding and optical element
JP2006248897A
Optical glass, preform and optical element
JP2012240909A